One-step hydrothermal synthesis of chiral carbon dots and their effects on mung bean plant growth. Issue 26 (27th June 2018) - Zhang, Mengling; Hu, Lulu; Wang, Huibo; Song, Yuxiang; Liu, Yang; Li, Hao; Shao, Mingwang; Huang, Hui; Kang, Zhenhui
Abstract : Chiral carbon dots were obtained by using a one-step hydrothermal method and promote the growth of mung bean plants. Abstract : Chiral compounds/materials have important effects on the growth of plants. Chiral carbon dots (CDs), as an emerging chiral carbon nanomaterial, have great potential in bio-application and bio-nanotechnology. Herein, we report a hydrothermal method to synthesize chiral CDs from cysteine (cys) and citric acid. These chiral CDs were further demonstrated to have systemic effects on the growth of mung bean plants, in which case bothl - andd -CDs can promote the growth of the root in mung bean plants, stem length of mung bean sprouts and water absorption of bean seeds. The elongation of mung bean sprouts presented an increasing trend with the treatment of chiral CDs of increasing concentration (below 500 μg mL −1 ). Furthermore, in the optimal concentration (100 μg mL −1 ), thel -CDs can improve root vigor and the activity of the Rubisco enzyme of bean sprouts by 8.4% and 20.5%, while thed -CDs increased by 28.9% and 67.5%. Due to more superior properties in improving root vigor and the activity of the Rubisco enzyme of mung bean sprouts, d -CDs are able to enhance photosynthesis better and accumulate more carbohydrate in mung bean plants.